Political cynicism among senior high school students of Santa Maria Catholic School Iloilo City. - Padilla, Ma. Aniceta (1993.)
This study is a case study on political cynicism of senior high school students and the bearing of three political socializing agents on political cynicism -- namely the family, the school and peers.
Thesis (Undergraduate, Bachelor of Arts in Political Science-History) College of Arts and Sciences, University of the philippines in the Visayas, Miagao, Iloilo.
Keywords: Students -- Senior High School -- Santa Maria Catholic School -- Iloilo City. -- Research